2016
DOI: 10.1177/1359105315600235
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in food-allergic versus healthy children and young adults

Abstract: Alexithymia is a multifaceted personality construct associated with several medical illnesses. However, no studies have focused on food allergy. We investigated alexithymia among food-allergic youths, compared to a matched healthy sample. A total of 220 participants aged 9-25 years were assessed using the Toronto Alexithymia Scale and the Alexithymia Questionnaire for Children. Food-allergic patients reported higher levels of alexithymia compared to a matched healthy sample. Furthermore, an association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 41 publications
6
8
0
Order By: Relevance
“…If we consider also borderline alexithymia, we reach the 47% of the sample. Results are in line with our previous study , which showed a significant difference in the frequency of non‐alexithymic individuals comparing food‐allergic patients with matched controls. Healthy participants reported a prevalence of 10% for alexithymia and 28% for borderline alexithymia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…If we consider also borderline alexithymia, we reach the 47% of the sample. Results are in line with our previous study , which showed a significant difference in the frequency of non‐alexithymic individuals comparing food‐allergic patients with matched controls. Healthy participants reported a prevalence of 10% for alexithymia and 28% for borderline alexithymia.…”
Section: Discussionsupporting
confidence: 92%
“…Alexithymia has been associated with an expanding range of somatic pathologies such as inflammatory bowel disease, myocardial infarction, chronic respiratory diseases, dermatologic conditions, chronic pain, neuromuscular disorders, diabetes and food allergy (). It has been found to increase unhealthy behaviours and susceptibility to organic diseases notably immune‐mediated disorders via physiological, behavioural, cognitive or social pathways from childhood leading to adverse outcomes in adulthood .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Withdrawal and cold/distant social functioning described in AAv have been linked to alexithymia (a multifaceted personality construct described as “a lack of words to express emotions”) . This is consistent with our previous studies finding higher levels of alexithymia in youth with food allergy …”
Section: Discussionsupporting
confidence: 91%